(untitled) - Graham Workman (Oxford, 1995)
The book deals with systematically with the four basic types of multi-word verbs. It introduces verbs and idioms in levely and amusing contexts. The book contains thirteen self-standing units, tapescripts, and an answer key
Keywords: english language - idioms,english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers,english language - verb phrase,listening - problems, exercises, etc